The Study of Anthropogenic Effect on the Intensification of Floods in Summer Catchment Basin, Case Study: Kan, Tehran ( - khadijeh heydarian; siavash shayan; Hossein jahantigh (تحقیقات کاربردی علوم جغرافیایی)
Summer catchment basins surrounding the city of Tehran, due to their remoteness from atmospheric pollution and urban manifestations, is considered as a place for exploring and recreating for many people, and as a place for money making out of restaurants attracting many tourists for others. Sangan is taken into consideration as one of the most beautiful valleys in Northwest of Tehran. The summer catchment basins due to the phenomenon of counter urbanization and also escape from city pollution, easy access, and short distance, has taken too much attention, so much that the inhabitants mostly spend winter in Tehran and summer there. Since some buildings have been built along the main river, the study of the effectiveness of riparian zone and also the specification of areas susceptible to flood is of great importance. In this research, using the HEC-RAS RAS model, flood- prone areas with different return periods (2 to 100 years old) were calculated, and then for the floodplain zoning the morphological characteristics of the flood zones gathered during the fieldwork have been used. The careful study of these flood fringe zones indicates that a small percentage of the lands are included in flood hazard zone with the 25-year return period. Also, the comparison of the pictures taken from the Sangan River in the past and present shows that the use of lands in the river bank has been changed and due to unauthorized constructions and gardening along the river, the width of the bed has dramatically been decreased. This factor increases the size of the floodplain area and consequently the damages.